Power Flow Calculation for Traction Networks under Regenerative Braking Condition Based on Locomotive-Traction Network Coupling - Wang Bin; Hu Haitao; Gao Shibin; Han Xudong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The regenerative braking technology is widely applied in high-speed electric multiple units (EMUs). And the voltage rise problem at end of the traction network would be caused by regenerative braking attracts more and more attention. The arm of this paper is to analyze the power flow calculation for EMUs under regenerative braking condition. Power flow calculation was done for two different EMU operation conditions by using a “locomotive-traction network” coupling model. In this model, a constant power load model on an all-parallel AT network multi-conductor chain circuit model is considerable. The simulation analysis shows that the iterative calculation method used in the present study is characterized by fast convergence and high accuracy, and is suitable to power flow calculation for traction networks under the braking condition and traction condition. It can be used to analyze voltage distribution, and the impact of traction load on power quality of the public power grid, etc. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2033